How pedagogical relations in early years settings are reconfigured by interactive touchscreens. (10th August 2021) - Samuelsson, Robin; Price, Sara; Jewitt, Carey
Abstract: While interactive touchscreens are currently entering into educational practice, little is known about what this means for learning in early childhood and, in particular, how touchscreens shape action and communication. In this paper, we examine the interactions of 2‐year‐olds and their teachers in a multilingual preschool in Sweden. We analyse the communicative environment between the children, teachers and shared touchscreens and books in the context of reading. A mixed‐methods analysis was used, taking a concept of action that includes both verbal, non‐verbal utterances and digital touch. The analysis shows a reconfiguration to the interactional dynamic where children perform comparable amounts of actions in sessions with the touchscreen and book reading but less talk during the touchscreen sessions. However, while talking less, children display other types of communicative actions. We analyse the changing interactional dynamic that follows, its implications to learning and early childhood pedagogical practice and how interaction can be reconceptualised as cycles of communication and action in which educational scaffolding unfolds. Practitioner notes What is already known about this topic Touchscreens are a significant part of children's lives and educational curricula. There is considerable uncertainty on how touchscreens can be incorporated into early childhood education. Little is known about how educational social interaction changes with touchscreens such as iPads. What this paper adds A mixed methods multimodal analysis of the changing actions and dynamics of iPads as compared with bookreading. Children's patterns of communication change towards less talk and more bodily communication, while teachers' actions remain somewhat similar. Touch actions change the dynamics of interaction, can alter the pedagogical situation and bring a reconceptualisation towards a cyclical and embodied view of interaction. Implications for practice and/or policy New patterns of action may require a recalibration of educational practices. Teachers need to attend to new sets of touch actions that children use to communicate and act with as displays of knowledge. The use of touch screens should be seen as complementary to established practices of language and literacy training (such as book reading) rather than replacing them.